2014
DOI: 10.1111/pme.12311
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Transversus Abdominis Plane Block for Acute Postoperative Pain Relief in Kidney Recipients: A Double-Blinded Clinical Trial

Abstract: Background. After renal transplantation, postoperative pain is usually mild to moderate. Postoperative pain is a concern and administration of systemic analgesic may be difficult because of underlying co-morbidities and variable responses of the graft. The transversus abdominis plane (TAP) block is one of the different approaches for postoperative pain relief following abdominal surgeries. We evaluated analgesic efficacy of TAP block on early postoperative pain by numeric rating scale (NRS) and morphine consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 14 publications
1
44
1
1
Order By: Relevance
“…In a systemic review and metaanalysis that was done by Gue et al they found that the PONV incidence and sedation scores were not significant difference between TAP block and wound infiltration in most included studies [3] No complication was reported in our study, however, TAP block has some complications including vascular, abdominal viscera and nerve injuries and block failure [25]. There are some limitations to our study.…”
Section: Discussioncontrasting
confidence: 39%
“…In a systemic review and metaanalysis that was done by Gue et al they found that the PONV incidence and sedation scores were not significant difference between TAP block and wound infiltration in most included studies [3] No complication was reported in our study, however, TAP block has some complications including vascular, abdominal viscera and nerve injuries and block failure [25]. There are some limitations to our study.…”
Section: Discussioncontrasting
confidence: 39%
“…One RCT reported that a US-guided lateral TAP significantly reduced 24-hour opioid consumption and pain scores compared with placebo; however, patients did not receive any coanalgesics. 104 In contrast, 2 other RCTs failed to show a significant impact of landmark-guided 105 or US-guided lateral TAP 106 on 24-hour opioid consumption or pain scores in patients receiving perioperative acetaminophen. Pain scores during the first 24 hours were low in all patients.…”
Section: Renal Transplantationmentioning
confidence: 99%
“…19,23,25,40,64,65 Transversus abdominal plane block did not reduce sixhour, 19,23,25 12-hr, 19,25,40 or 24-hr pain scores 19,23,25,40,65 ( Table 2). In comparison with placebo, the effect of the TAP block on morphine consumption at 24 hr 19,23,25,40 was also not significant (-14.2 mg; 95% CI, -30.6 to 2.2; P = 0.09)…”
Section: Transversus Abdominal Plane Block In Urologic Surgerymentioning
confidence: 99%
“…16,29,36,38,[40][41][42][43]52 Compared with the control group, TAP block showed no difference in reducing the six-hour pain score 16,29,36,38,41,43 (-0.1; 95% CI, -1.4 to 1.3; P = 0.95), 12-hr pain score 16,38,41,52 (1.9, 95% CI, -4.2 to 0.4; P = 0.11), 24-hr pain score 16,29,36,38,[41][42][43]52 (-0.8; 95% CI, -2.0 to 0.4; P = 0.18), or 24-hr morphine consumption 16,29,36,38,43,52 (-14.7 mg; 95% CI, -37.8 to 8.4; P = 0.21) ( Table 2). Only one trial 16 performed TAP block from inside the abdominal wall; consequently, it was not possible to perform subgroup analysis for this comparison.…”
Section: Transversus Abdominal Plane Block In Abdominal Surgerymentioning
confidence: 99%
See 1 more Smart Citation